UPAYA PENURUNAN DAN PENCEGAHAN STUNTING PADA ANAK: PROGRAM KERJA KELOMPOK KKN 65 DIDESA BENTENG - Basri, Muhammad; Bancin, Eliyas Santi; Bara, Sarah Kumala B; Budiman, Mutya Fradilla; Muthe, Putri Naimah; Hasibuan, Ernida; Tanjung, Erma Yanti; Pohan, Wahyuni; Julia, Ayu Putri; Fakhlevi, Akmal; Tarigan, Bima (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
Community Service (KKN) activities in the village have become important in preventing stunting in children. Various interaction and instruction activities have been carried out to strengthen the community's awareness of the main nutrition in children, especially in the first 1000 days of life. The method carried out regarding stunting is by conducting offline seminars while providing knowledge about stunting and also participating in preventing stunting, namely through the integrated health post (Posyandu). KKN has educated the community about the meaning of stunting, its characteristics, and its impacts. The speaker from one of the KKN students from the Guidance and Counseling department has explained stunting and how to prevent it and conducted a question and answer session to strengthen the community's awareness of the main nutrition in children. KKN activities also focus on the role of parents, especially in empowering mothers by providing knowledge about MPASI (Complementary Foods for Breast Milk) and the importance of providing additional food for toddlers. This aims to reduce the number of stunting in Benteng village. Stunting counselling activities in the village involve health checks from the Integrated Health Post (Posyandu). This aims to strengthen the awareness of the community's insight into the main nutrition in children and how to prevent it. Thus, KKN activities in Benteng village have played an important role in increasing public awareness of stunting and its prevention and reducing stunting rates in the area.